Design Optimization of Waveguide Bends in Photonic Crystals - Bettini, P.; Boscolo, S.; Specogna, R.; Midrio, M. (IEEE transactions on magnetics, 2009)
In this paper, a fast and robust optimization scheme is presented and applied to the optimal design of planar photonic crystals. It is based on a parallel hybrid (stochastic-deterministic) algorithm coupled to a semi-analytic solution of ldquofull Maxwellrdquo equations by multiple scattering technique. The numerical results of the optimal design of different waveguide bends are presented.